FREQUENCY OF SPREAD OF BRONCHIAL ASTHMA AMONG MIDDLE-AGED PEOPLE AND EFFECTIVENESS OF TREATMENT. Almaty, City Clinical Hospital No. 1 - Kuralsynova Marzhan; Bakytova Aidana; Omarova Kh.S. (World Science, 2022)
Bronchial asthma (BA) is a global problem. The incidence of bronchial asthma is growing all over the world. It is among the top ten noncommunicable chronic diseases, which are the main cause of death among people, reducing life expectancy by 6.6 years for men and 13.5 years for women.